PENERAPAN PEMBELAJARANMODEL JIGSAW UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS V SD NEGERI 2 KARANGSARI PADA TEMA 1 SUB TEMA 3 - As'ad Ainur Rofiq; Adzimatnur Muslihasari (STKIP Persada Khatulistiwa Sintang, 2020)
Student activeness in the learning process is very important to acquire knowledge and skills. Based on the results of observations made by researchers during thematic learning in class V SD Negeri 2 Karangsari on Saturday, January 4, 2020, the results of student activity and learning outcomes were still low. This can be seen from the activeness indicators: 1) students who are included in the active category are 5 students (30%), 2) students who are quite active are 3 students (20%),3) students who are in the less active category are 8 students (50%). This research was conducted to determine how the application of the Jigsaw model increases student activity. The activity observed is mental activity which includes responding to, remembering and solving problems. The research subjects were 16 grade V SD Negeri 2 Karangsari students. Student activeness is said to increase ≥75% of students reach the active and very active category, it is expected that the results of the implementation of teacher and student activities are at least 85%. The results showed that the average activity of students in the first cycle was 65% and the second cycle was 91% on average. The results of observations of the implementation of the activities of teachers and students in cycle I 79% and cycle II 93%, based on the data, the application of the Jigsaw model of learning can increase learning activeness in theme 1 sub theme 3.